Board Composition, Strategic Leadership and Firm Performance: A Study of Commercial Banks in Kenya - Masaga, Barante; Arasa, Robert; Nzioki, Susan (IJBMM, 2019)
Boards of Directors are not only expected to monitor a company management; they are also held responsible for an organization’s failure to attain organizational performance goals.The purpose of this study was to establish the relationship between board of directors’ composition, strategic leadership and performance of commercial banks in Kenya. The specific objectives were to establish the relationship between board size, non-executive directors, and board diversity and performance of commercial banks in Kenya and the extent to which strategic leadership moderates such relationships. This study was anchored on Agency theory and Resource Dependence theories. The study employed a correlational research design. The target population was all operational registered commercial banks in Kenya which are thirty nine (39) in number. Purposivesampling technique was utilized to pick target respondents (Chief Executive Officers and one non-executive director for each bank). Data was collected using questionnaires. Ordinal logistic regression analysis was performed on the data collected using R technique to estimate and provide empirical evidence on the nature of relationship between the bank performance and Board composition. The research hypotheses were tested by determining the significance of the regression coefficients of the estimated models. Board size, incorporation of non-executive directors to the board, embracement of strategic leadership was found to have a positive and significant relationship with the performance of commercial banks in Kenya. Based on the findings, the study recommends that; Banks should constitute boards whose sizes are relative to the size of the banks, the boards so constituted should reflect diversity in terms of professional background, gender and ethnicity,valuable balance between executive and non-executive directors; Boards of Directors should offer strategic leadership by drawing strategic plans detailing clear strategic objectives on key areas of operation, disseminating the same to bank employees for buy in and smooth execution of the same. Further, banks should employ people with strong strategic orientation especially at the top level management and invest resources in developing capacity for strategic leadership.
Keywords: Board Diversity; Board of Directors; Board Size; Firm Performance; Strategic Leadership.